Subordinated Debt Under Bail-in Threat - Edoardo Martino (University of Bologna Law Review, 2018)
This paper aims to address the role of subordinated liabilities within the newresolution framework resulting from the post-crisis reforms. In particular, this study starts from the resolution intervention of four Italian banks in November 2015. The legal analysis of that resolution is complemented by an empirical analysis of the determinants of subordinated debt issuances for Italian banks. From this set of evidence is possible to infer the desirability of a well-functioning and dynamic market for subordinated debt. On the other hand, what clearly emerges is the incompatibility between such a market and the new regulatory framework as it is. Therefore, the paper, given the compelling arguments showing the inefficiency of a pure mandatory bail-in mechanism for subordinated debt, proposes to complement it with a contractual clause to bail-in subordinated creditors, tailored on coco bonds model, in order to enhance certainty amongst the contractual parties.